PEMBUATAN INFOGRAFIS DUSUN KRAJAN I - Harjito, Dwipraptono Agus (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Citizen need to know statistics of their area, but not all citizens are able to understand the statistics in the form of numbers, which is complicated, it needs to be tranform into an infographic. Then, writer perform community service in the form of making infographics to illustrate the condition of dusun Krajan.